Intra-organizational knowledge transfer in a Finnish multinational company - Tuomela, Minna (My University, 2012)
The ability of a multinational company to effectively transfer knowledge from one unit to another can create a great source of competitive advantage and is crucial for long-term success. However, in their attempts to disseminate existent knowledge across national boundaries, organizations encounter several obstacles. Especially challenging is the transfer of tacit knowledge, the most valuable kind, as it is embedded in the minds and the behavior of people. The purpose of this study is to identify the main factors and challenges to be considered in intra-organizational knowledge transfer and consequently develop a framework that could be utilized to improve the process. The research is of qualitative nature and it adopts an exploratory approach. The study was further conducted as an intensive single-case study through studying a Finnish multinational company, and the researcher adopted a role as a participant observant in the research setting. Other data collection methods include semi-structured interviews and an online survey. The research findings show that knowledge transfer is currently challenging within the international sales organization of the case company. The majority of knowledge is currently concentrated in the company headquarters, and it is not always systematically distributed to the regional offices abroad. The main factor affecting knowledge transfer seems to be the organizational culture, which does not support or encourage knowledge sharing. The company is struggling in having a common place for information and employees that lack proper social networks have difficulties accessing relevant knowledge. Some recommended improvement suggestions include the institutionalization of knowledge transfer by turning it into an articulated organizational goal, and the implementation of a reward system that includes soft factors, such as teamwork and knowledge sharing behavior. Furthermore, the organizational culture should be more open and supportive in order to reinforce trust. Individuals in regional offices should be given better support by offering them dedicated mentors and increasing the amount of expatriation. Finally, knowledge should actively be codified and stored in commonly shared platforms where it is easily accessible by all employees.